An experimental investigation on the effect of Al2O3/ cutting oil based nano coolant for Minimum Quantity Lubrication drilling of SS 304 - Dattatraya G. Subhedar; Yashkumar S. Patel; Bharat M. Ramani; Gajanan S. Patange (Cleaner Engineering and Technology, 2021)
Now a day's energy has the most important input for the growth of any system. Today energy demand has rapidly increased across all sectors, including agriculture, transport, residential, commercial and industry. To deal with these issues in many production processes, the effective cutting fluid pays an important role in reducing the friction force between the cutting tool and work piece surface. In this study we explore the experimental investigation to study the potential of Al2O3 Nano particles/Mineral oil-based cutting fluid during drilling of Stainless Steel 304 on tool life and the surface roughness. During investigation two step method is used to synthesis the Nano cutting fluid by using Al2O3 nanoparticles with volume fraction 0.3,0.8 and 1% in metal cutting fluid. Ultrasonic agitation force is used to achieve stability of Nanofluid. The Drilling operation on vertical CNC machine for 1000 rpm and 1500 rpm speed at constant feed rate of 0.050 mm/rev. Result shows that the Nano coolants increases the tool life and reduces the surface roughness. Tool life is observed highest for Nano cutting fluid of 1% volume fraction and achieve the lowest surface roughness 2.01 μm at 1000 rpm. The derived results are witnessing the usability of nano coolant.